Determining Experience Quality on Customers' Perceived Value, Satisfaction and Loyalty - Juliana, Juliana; Pramono, Rudy; Sartjie, Indriany; Roon, Jocelyn; Orlina, Meita; Daicy, Venessa (LP3M Universitas Putra Bangsa, 2022)
It is essential in the hospitality and tourism industries to meet the gastronomic expectations of travelers. The purpose of this study is to investigate the impact of customer perceived value on customer loyalty and satisfaction, experience quality on customer perceived value and loyalty and investigate the impact of customer satisfaction on customer loyalty. Survey questionnaires were delivered to 201 participants in Tangerang City. The design of the sample used in this study was nonprobability sampling with a technique of purposive sampling with the criteria that you have had culinary tours in Tangerang at least 2 times a year. Data collection was obtained for 3 months Descriptive statistics and PLS-SEM were used to analyze the data. This is a quantitative descriptive analysis. The result show that Customer perceived value have a positive and significant effect on customer loyalty and customer satisfaction, experience quality have a positive and significant effect on customer perceived value, customer satisfaction have a positive and significant effect on customer loyalty. The study findings have one hypothesis is not supported. The study's findings will be useful guides for hospitality and tourism in building a more strategically situated approach to customer satisfaction.